2018
DOI: 10.1371/journal.pone.0199962
|View full text |Cite
|
Sign up to set email alerts
|

Upper nasal hemifield location and nonspatial auditory tones accelerate visual detection during dichoptic viewing

Abstract: Visual performance is asymmetric across the visual field, but locational biases that occur during dichoptic viewing are not well understood. In this study, we characterized horizontal, vertical and naso-temporal biases in visual target detection during dichoptic stimulation and explored whether the detection was facilitated by non-spatial auditory tones associated with the target’s location.The detection time for single monocular targets that were suppressed from view with a 10 Hz dynamic noise mask presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 68 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…Considering first the research most comparable to our work here (i.e., investigating the nasotemporal asymmetry in IOC), we find little consensus in the handful of studies dedicated to this line of investigation. Whereas some studies show an advantage for the nasal VHF 25 27 , other studies showed either no, mixed, or even opposite results regarding the dominance of nasally versus temporally presented stimuli in IOC 28 30 , 41 , 42 . Regardless, the current study provides decisive results as we show a robust advantage for the nasal VHF during IOC evoked by b-CFS, across 300 + observers in five independent datasets.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Considering first the research most comparable to our work here (i.e., investigating the nasotemporal asymmetry in IOC), we find little consensus in the handful of studies dedicated to this line of investigation. Whereas some studies show an advantage for the nasal VHF 25 27 , other studies showed either no, mixed, or even opposite results regarding the dominance of nasally versus temporally presented stimuli in IOC 28 30 , 41 , 42 . Regardless, the current study provides decisive results as we show a robust advantage for the nasal VHF during IOC evoked by b-CFS, across 300 + observers in five independent datasets.…”
Section: Discussionmentioning
confidence: 94%
“…The first thing to note in this respect is that, in our current study, we have concerned ourselves exclusively with b-CFS. Interestingly, of the studies investigating nasotemporal asymmetries, the one using a b-CFS paradigm (as opposed to other studies in the literature using conventional BR measures) also finds a strong advantage for visual information in nasal VHF locations 27 . Why then, do the results from the two b-CFS studies differ from studies applying other paradigms evoking IOC (e.g., BR)?…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation